Large Right Atrial Thrombus Associated with Central Venous Catheter Requiring Open Heart Surgery - Nasir Hussain; Paul Eric Shattuck; Mourad Hussein Senussi; Erwin Velasquez Kho; Mubeenkhan Mohammedabdul; Devang K. Sanghavi; Usman Mustafa; Arvind Balavenkataraman; Dragic M. Obradovic (Case Reports in Medicine)
Central venous catheters (CVC) are used commonly in clinical practice. Incidences of CVC-related right atrial thrombosis (CRAT) are variable, but, when right atrial thrombus is present, it carries a mortality risk of 18% in hemodialysis patients and greater than 40% risk in nonhemodialysis patients. Different pathogenic mechanisms have been postulated for the development of CRAT, which includes mechanical irritation of the myocardial wall, propagation of intraluminal clot, hypercoagulability, and hemodynamics of right atria. Presentation of CRAT may be asymptomatic or may be associated with one of the complications of CRAT like pulmonary embolism, systemic embolism, infected thrombi, or hemodynamic compromise. There are no established treatment guidelines for CRAT. We describe an interesting case of a 59-year-old asymptomatic male successfully treated with open heart surgery after failure of medical treatment for a large CRAT discovered during a preoperative evaluation for a kidney transplant. Our case underscores that early detection of CRAT may carry a favorable prognosis as opposed to waiting until catastrophic complications arise. It also underscores the importance of transesophageal echocardiography in the detection of thrombus and perhaps guides clinicians on which treatment modality to be used according to the size of the thrombus.